Effect of Prenatal Gentle Yoga On Anxiety Levels Of Trimester Pregnant Women III In Clinic Pratama Cahaya 2 Lubuk Pakam - Dodid Nurianto; Nurul Amalia Tanjung (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Pregnancy is a condition where women experience different physiological changes and stress and are accompanied by unique physical and psychological demands. These changes can cause discomfort in pregnant women such as dyspnea, insomnia, gingivitis and epulis, frequent urination, perineal pressure and discomfort, back pain, constipation, varicose veins, fatigue, Braxton hicks contractions, leg cramps, ankle edema, and changes in mood and increased anxiety. Anxiety and depression in pregnancy is a problem with a fairly high prevalence, which is around (12.5-42%) and it is even estimated that this disorder will become the second biggest cause of illness in 2020 (Putri, 2019). To find out